A Qualitative Content Analysis on MilkLife Instagram Towards Awareness of Lactose-Free Milk on Urban Indonesian Consumer - Herdian, Rizal BD; Syafitri, Mirza; Fauzi, Almira N (Yayasan Ilomata, 2024)
In Indonesia, up to 60% of people suffer from lactose intolerance therefore creating lactose-free milk by Milk Life is a vital option. However, despite its benefits, sales are not reaching the brand’s expectations, suggesting the Indonesian market is yet to be fully tapped. This research examines Milk Life's Instagram marketing strategies aimed at enhancing awareness and sales of its lactose-free milk product. Utilizing qualitative research methodology, particularly in-depth interviews for data collection and analysis, it investigates the efficacy of these marketing endeavors in educating consumers and influencing their purchasing behaviors. Upon data collection, the analysis is conducted manually, involving careful examination of interview results, linking them to research questions, and interpreting them in an interpretive manner. Results reveal a significant lack of awareness about lactose intolerance and Milk Life's products, attributed to the current digital marketing approach, which led to low purchase intentions. The study highlights an urgent need for better digital marketing strategies and communication to inform the Indonesian public about the advantages of lactose-free milk. Enhancing online visibility and education could improve market growth and meet the needs of lactose-intolerant individuals. This research emphasizes the role of targeted digital marketing to increase the reach and acceptance of lactose-free milk in Indonesia.